Modelo de avaliação competitiva de destinos turísticos com base nas capacidades dinâmicas - Justa, Roberto Pascarella (2008)
Over the past few decades, the phenomenon of competitiveness, and the underlying competitive advantage thereof, has been analyzed in diverse ways, in terms of its sources (external and internal environment) and competitive management strategies, as well as different scopes (nations, economic sectors and organizations) and fields of study (economy and organizational theory). Moreover, competitiveness is a complex phenomenon and, thus, reflected in the many methods and approaches which some frameworks have developed throughout the period to try to examine it in the tourism sector as well as other industries. In this research a framework for destinations is presented on the basis of dynamic capabilities. This is an important contribution to the research, since previous studies for the tourism sector have not approached this relevant aspect of the competitive development of tourist destinations, i.e. based on the capabilities of innovation, transformation, creation and research presents a competitive evaluation of the dynamic capabilities of tourist destinations, on the basis of 79 activities, distributed in eight , this work presents an empirical application of the framework in a sample of twenty Brazilian cities, considered, by the Brazilian Tourism Minister, as indicative tourist destinations for regional development. The results obtained from this evaluation were submitted to tests of statistical reliability and have demonstrated that the destinations possess heterogeneous levels of capabilities between themselves (different levels developed in the categories between the cities) and inside each destination (developed levels of capability between the categories of the destination). In other words: heterogeneity is not only between category to category.